Simulated auditory nerve response evoked by lateral-wall and peri-modiolar electrode arrays inserted in scala tympani or scala vestibuli - Wenger, Cornelia; Fellner, Andreas; Rattay, Frank (Frontiers in Neuroscience, 2025)
IntroductionCochlear implants (CIs) are neuroprosthetic devices designed to restore hearing in individuals with severe to profound hearing loss. Clinically, CI electrode arrays differ by location, either peri-modiolar (pm) positioned near the cochlear axis, or lateral-wall (lw), placed closer to the peripheral terminals of auditory nerve fibers (ANFs). Standard insertion is into the scala tympani (ST), though the scala vestibuli (SV) is considered for cases of severe ST ossification.MethodsThis computational study investigates the neural responses of both healthy and degenerated ANFs to monopolar stimulation from electrode arrays at different locations. Using a 3D finite element model of the human cochlea, we evaluated threshold excitations for short monophasic pulses across 25 traced ANF pathways. Four array configurations were compared (pmST, pmSV, lwST, lwSV), each with electrodes directly targeting the traced fibers.ResultsResults show that excitation thresholds and stimulation specificity depend on both neural health and array position. Specificity, defined by minimizing off-target fiber stimulation, was highest for healthy ANFs with lwSV, followed by pmST, lwST, and pmSV, influenced by electrode orientation. Simulated ST ossification, modeled as decreased conductivity, generally led to reduced cathodic thresholds, suggesting that ST insertion may still be advantageous even with developing or partial ossification.DiscussionThe pmST array consistently offered reliable outcomes across varying electrode configuration and neural conditions. These findings support considering SV insertion when ST is obstructed and highlight factors influencing CI performance based on array location and neural status.